Generative AI and Effectiveness of Deepfake Detection: Analysis of the effectiveness of deepfake detection capabilities between artificial intelligence and the human brain. - Rodriguez Egas, Nathalie Alejandra; Gómez González, Daniel; Sierra Sánchez, Javier; Medranda Morales, Narcisa Jessenia (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2026)
Artificial intelligence has revolutionized multiple industries, particularly in the generation of images and videos. The emergence of tools capable of creating hyper-realistic videos poses serious risks in identity theft. This article examines the phenomenon of deepfakes and, factors that influence their identification, and presents an experimental study that evaluates the effectiveness of detecting these contents using deep neural networks. It compares the performance of a group of people with a tool based on deep learning technology, providing a detailed analysis of the strengths and limitations of both approaches.